1985
DOI: 10.3171/jns.1985.63.3.0448
|View full text |Cite
|
Sign up to set email alerts
|

Vicryl (polyglactin 910) mesh as a dural substitute

Abstract: Many substances have been used as dural substitutes. Although the various materials are effective in a variety of settings, a material that is absorbed over time, elicits minimal inflammatory reaction, is relatively inexpensive, and is easily manipulated would be beneficial. An experimental project was conducted involving closure of dural defects in dogs with a Vicryl (polyglactin 910) mesh graft. Macroscopic and histological examination performed at various times after placement revealed resorption of the gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 16 publications
0
28
0
4
Order By: Relevance
“…The Vicryl mesh used is an absorbable material made of polyglactin, which has a degradation time of 6 to 8 weeks. It has been used with good results in pelvic floor reconstruction, splenorraphy, and closure of dural defects [26][27][28][29]. When similar material was used as an onlay to reinforce abdominal wound closures, wound strength has been shown to increase compared with primary closure alone [30].…”
Section: Discussionmentioning
confidence: 99%
“…The Vicryl mesh used is an absorbable material made of polyglactin, which has a degradation time of 6 to 8 weeks. It has been used with good results in pelvic floor reconstruction, splenorraphy, and closure of dural defects [26][27][28][29]. When similar material was used as an onlay to reinforce abdominal wound closures, wound strength has been shown to increase compared with primary closure alone [30].…”
Section: Discussionmentioning
confidence: 99%
“…14,24,41 The suture fibers were chosen because a previous clinical study showed that these fibers had significant potential as an absorbable dural substitute with minimal inflammatory reaction. 42 These large-diameter fibers provided significant strength and toughness to the implant for several weeks. 24 Then, long cylindrical macropores of 293 Ϯ 46 m in diameter were created in CPC after fiber dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to be completely resorbed after a period of three months. The material is replaced with fibrous collagenous tissue, and minimal inflammation is associated with this process [14,[19][20][21][22]. Subsequently, indications for its use were extended to the orbital floor [6,14].…”
Section: Introductionmentioning
confidence: 99%